2019
DOI: 10.1159/000499436
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Trial Assessing the Oral Administration of a Heat-Treated <b><i>Lactobacillus paracasei  </i></b>Supplement in Infants with Atopic Dermatitis Receiving Topical Corticosteroid Therapy

Abstract: <b><i>Background/Aims:</i></b> Atopic dermatitis (AD) is a common disease in infancy, for which topical steroids are the first-line therapy but have side effects. Innovative approaches are needed to reduce the burden of AD and corticosteroid usage in infants. <b><i>Methods:</i></b> The once-daily consumption of heat-treated probiotic <i>Lactobacillus paracasei</i> GM-080 or placebo for 16 weeks as supplementary approach to topical treatment with fluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…The ccl2 promoter was strongly methylated in monocytes, for both exposure times and in different sites, while the mixture did not exert any effect on ccl2 promoter methylation in keratinocytes. In fact, our data agree with literature that ccl2 gene promoter methylation is widely reported in human monocytes in vitro and in vivo, whereas no evidence can be found for the methylation of the ccl2 promoter in keratinocytes (56,57). This can be explained by taking into account that the transcriptional regulation of ccl2, in the context of non-resolving inflammation, appears to be more related to histone modification (58,59).…”
Section: Discussionsupporting
confidence: 89%
“…The ccl2 promoter was strongly methylated in monocytes, for both exposure times and in different sites, while the mixture did not exert any effect on ccl2 promoter methylation in keratinocytes. In fact, our data agree with literature that ccl2 gene promoter methylation is widely reported in human monocytes in vitro and in vivo, whereas no evidence can be found for the methylation of the ccl2 promoter in keratinocytes (56,57). This can be explained by taking into account that the transcriptional regulation of ccl2, in the context of non-resolving inflammation, appears to be more related to histone modification (58,59).…”
Section: Discussionsupporting
confidence: 89%
“…However, the amount of topical corticosteroids showed no difference between groups, nor was there any significant difference noted in the overall symptom‐free duration 5 . Yan et al demonstrated that the probiotic L paracasei (1 × 1010 CFU daily) was not beneficial as a complementary approach to topical corticosteroids in infants with AD; however, slight beneficial effects may have been masked by the moderate potency of the corticosteroid used 6 …”
Section: Resultsmentioning
confidence: 99%
“…This review includes 22 trials involving 1420 children ranging from 1 month to 18 years old with atopic dermatitis. Twenty‐one studies were double‐blind, randomized, placebo‐controlled trials on the use of various probiotic strains for the treatment of pediatric atopic dermatitis 23‐43 . One study was a randomized trial comparing probiotic strains to no treatment 44 .…”
Section: Resultsmentioning
confidence: 99%